Orientasi Kognitif dan Harapan Perempuan Etnis Tionghoa Kota Padang terhadap Kepolitikan Pasca Orde Baru - Sari, Estika (Jurnal Demokrasi, 2011)
Political issue of New Order era has caused a "trauma" for certain groups such as women, especially Chinese women who in fact are lagging far away from political life. This article seeks to describe the political orientation of Chinese ethnic, especially on cognitive orientations and expectations towards the political issues after new order era. The finding of this study showed that cognitive orientation of Chinese women are still superficial and far from the expectation. The hope toward the current politic is that they could be more involved in any political empowerment. Kata Kunci: Orientasi Kognitif, perempuan etnis Tionghoa, kepolitikan pasca Orde Baru